PENGEMBANGAN LMS BERBASIS GOOGLE SITES UNTUK MENGEMBANGKAN HOTS SISWA PADA MATA PELAJARAN GEOGRAFI - Devin Ardhi Saputra; Nofrion Nofrion (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2022)
This research aims to analyze the development of LMS based on Google Sites in Geography subject. The development of this LMS is intended to improve students' higher order thinking skills (HOTS) which can be used for online and offline learning. There are two research methods used i.e. ‘development research’ to develop a valid, practical, and effective Google Sites-based LMS and ‘experimental research’ to prove the effectiveness of Google Sites-based LMS in improving students' HOTS. The development model used is the Plomp which consists of three phases i.e. the Initial investigation phase, the Prototype development phase, and the assessment phase. Then a validity test is carried out involving three lecturers as validators, i.e. validation of media expert, material expert, and language and design expert with "Valid" result. To determine the effectiveness of this LMS, an independent samples test of learning outcomes for the control class and the experimental class is conducted. The control class is class XI IPS 2 with 36 students, consisting of 20 male students and 16 female students who do not use LMS and the experimental class is class XI IPS 3 with 36 students, consisting of 20 female students and 16 male students who use LMS based on Google Sites. The results of the research prove that Google Sites-based LMS is "Valid and Practical" so that it can be used in learning Geography to improve students' HOTS. The results of independent samples test prove that the significance value (2-tailed) is 0.000 < 0.05 significance value, meaning that there is a difference between the experimental class and the control class. A difference in the average score between both classes means that the students who study using this LMS based on Google Sites have better learning outcomes than the students who don’t.